Cryptococcal meningitis in apparently immunocompetent patients: association with idiopathic CD4+ lymphopenia. Issue 2 (9th December 2017) - Shribman, Samuel; Noyce, Alastair; Gnanapavan, Sharmilee; Lambourne, Jonathan; Harrison, Thomas; Schon, Frederick
Abstract : We present two cases of cryptococcal meningitis in people subsequently diagnosed with idiopathic CD4+ lymphopenia. Both presented with new onset headaches without sinister features and were sent home on multiple occasions from emergency departments. Cryptococcal meningitis in HIV-negative patients poses major diagnostic and management problems; the associated mortality is 9%–27%. We suggest performing blood and cerebrospinal fluid cryptococcal antigen tests in all people with lymphocytic meningitis.